Analysis of Legal Uncertainty for Medical Personnel and Human Rights Violations in the Practice of Female Genital Mutilation in Indonesia - Ferry Anggriawan (MLJ Merdeka Law Journal, 2025)
Female genital mutilation is a practice permitted according to some Islamic legal norms and some customary laws in Indonesia, but this practice contradicts legal norms, including Article 102 letter a of Government Regulation No. 28 of 2024 concerning the Implementation of Law No. 17 of 2003 concerning Health, as well as Article 4 and Article 49 paragraph 2 of Law No. 39 of 1999 concerning Human Rights. From this background, the author attempts to analyze how legal certainty is analyzed for medical and non-medical personnel regarding the practice of female circumcision regulated in Article 102 letter a of Government Regulation No. 28 of 2024 concerning the Implementation of Law No. 17 of 2003 concerning Health, and how the analysis of female circumcision practices can be categorized as a form of discrimination against women according to Law No. 39 of 1999 concerning Human Rights. This research uses normative legal research with a case study approach and regulatory comparison to identify existing inconsistencies and legal gaps. The results of this study are that medical personnel performing female circumcision in Indonesia face legal certainty, being free from criminal sanctions, but are at high risk of facing severe professional disciplinary sanctions and civil lawsuits, as the practice contradicts national health policies and medical ethics. Furthermore, Article 4 of Law No. 39 of 1999 on Human Rights states that the state should guaranty protection for non-derogable rights, but the regulatory reality is that the state still allows this. The next conflict is found in Article 49 Paragraph (2) of Law No. 39 of 1999 on Human Rights. Fundamentally, this practice violates women's right to bodily integrity and health, so the state must provide clear legal certainty and protection to women, in line with the broader protection goals of the Human Rights Law.